A Case of Pacemaker Endocarditis Caused by Aerococcus urinae - Sandra Samuelsson; Charles Kennergren; Magnus Rasmussen (Case Reports in Infectious Diseases)
Background. Aerococcus urinae has lately been acknowledged as a cause of infective endocarditis (IE) especially in older males with underlying urinary tract disorders. In this population, cardiac implanted electronical devices (CIED) are not uncommon, but despite the capacity of A. urinae to form biofilm in vitro, no cases of aerococcal CIED infections have been reported to date. Case Presentation. An 84-year-old male with pacemaker was admitted with dysuria one month after a transurethral procedure for urinary bladder cancer. A. urinae was isolated from urine and blood. Transesophageal echocardiography (TEE) was without signs of vegetation on valves or pacing cables. The patient was treated with a twelve-day course of β-lactam antibiotics. Forty days after the initial admission, the patient was readmitted due to malaise, general pain of the joints, chills, and renewed blood cultures grew A. urinae. TEE demonstrated a 10 × 5 mm vegetation on either the tricuspid valve or one of the pacing cables. The pacemaker system was completely removed and demonstrated macroscopic signs of infection. A temporary system was implanted, and after 14 days of penicillin G treatment, a new system permanent system was implanted. Total treatment time was 40 days. Recovery was uneventful. Conclusion. This report demonstrates that A. urinae can cause CIED infection. In patients with A. urinae bacteremia and a CIED, this risk must be considered, especially if bacteremia reoccurs.